THE EFFECT OF GAME-BASED LEARNING MODEL ASSISTED BY BAMBOOZLE ON THE MULTIPLICATION SKILLS OF ELEMENTARY SCHOOL STUDENTS - Irma Retno Rahayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Students’ skills in performing multiplication operations are low. The purpose of the study in this article is to determine the effect of the game-based learning model assisted by